KERAGAMAN JENIS VEGETASI PADA HUTAN DATARAN RENDAH WILAYAH ADAT AIR BUAYA PULAU BUANO KABUPATEN SERAM BAGIAN BARAT - Yulianus D. Komul; Jopie Christian. Hitipeuw (JURNAL HUTAN PULAU-PULAU KECIL, 2021)
The research was carried out in the Air Buaya forest area, which is a forest area where the use of forest products is controlled by Soa Nuru Na'ani and Sulipatan who are part of the Buano Island indigenous community with lowland secondary forest cover. The purpose of this study was to determine the diversity of vegetation types. This research has been carried out using a survey method with a combination of the Line Method (Continuous Trip Sampling) and the Line Plot Sampling method to make an inventory of all potential vegetation in the research location. The research area is 1 hectare (10,000 M2) with the specified line length 500 and the line width 20 meters. The results showed 30 species with 243 individuals for timber forest products which were divided into 26 families and 8 species with 129 individuals for non-timber forest products. The value of the important value index was controlled by the type of tongka langit (Ailantus integrifolia) which came from the Simaroubaceae family with a value of 63.4717 % and the species diversity index calculated according to Shanon Winner 1954 was at a value of 1.2945% with the category of species diversity of timber forest products for the study site in condition currently